XX sex chromosome complement promotes atherosclerosis in mice - Yasir AlSiraj (Nature Portfolio, 2019)
Men and women differ in their risk of developing coronary artery disease, in part due to differences in their levels of sex hormones. Here, AlSiraj et al. show that the XX sex genotype regulates lipid metabolism and promotes atherosclerosis independently of sex hormones in mice.